WHICH INFORMATION TO CONSENT TO RESEARCH? FROM A FIELD ANALYSIS IN PEDIATRIC ONCOGENOMICS TO AN APPROACH TO IMPROVE INFORMATION SUPPORTS THROUGH A COLLABORATIVE APPROACH BETWEEN INSTITUTIONS, RESEARCHERS AND PATIENT ASSOCIATIONS - DE MONTGOLFIER, Sandrine (MEDECINE LEGALE DROIT MEDICAL, 2025)
One of the basic principles of medical ethics since the Belmont Report of 1979 is based on the search for autonomy of the person by signing the consent in a free and informed manner. This would imply that the information given to the persons concerned by a research project or the proposal of a genetic test be understandable, appropriate and therefore understood so that informed consent can be given. For children and persons with intellectual disabilities, our legal framework advocates adapted information and delegation of consent to a legal guardian or parental authority. However, it is clear that current information and consent forms do not meet these criteria for adults and even more so for children: they are often very dense, used to convince rather than to explain, and not very well suited to a shared decision-making process. Many research projects are underway to try to meet the challenge of making information accessible to all in the field of health literacy, in the design of decision support documents. We will report from a particular field, that of pediatric onco-genomics, how consent is perceived, but also expected by the people concerned (health professionals, parents and children). Based on this empirical ethical work, we will report on the ethical issues of consent in research and particularly research involving genetic analyses in children. We will introduce how this work is being pursued by a participative work initiated under the impulse of INSERM and the France Genomic Medicine Plan, with representatives of patient associations of diseases concerned with childhood or intellectual disability, professionals (jurists, geneticists, researchers in medical ethics) and a designer, to review and adapt information and consent documents to research or genomics in children.